Geno5mC: A Database to Explore the Association between Genetic Variation (SNPs) and CpG Methylation in the Human Genome. Issue 11 (28th May 2021) - Gómez-Martín, C.; Aparicio-Puerta, E.; Medina, J.M.; Barturen, Guillermo; Oliver, J.L.; Hackenberg, M.
Graphical abstract: Highlights: DNA methylation and genetic variation was obtained from 58 WGBS datasets. 51, 585 SNPs were found as statistically associated to CpG methylation levels. geno 5 mC includes associations for SNPs vs. CpGs and CpGs vs. gene expression. geno 5 mC aids to find possible molecular mechanisms for trait associated SNPs. We report a bowel disease SNP associated to CpGs located in inflammatory genes. Abstract: Genetic variation, gene expression and DNA methylation influence each other in a complex way. To study the impact of sequence variation and DNA methylation on gene expression, we generated geno 5 mC, a database that contains statistically significant SNP-CpG associations that are biologically classified either through co-localization with known regulatory regions (promoters and enhancers), or through known correlations with the expression levels of nearby genes. The SNP rs727563 can be used to illustrate the usefulness of this approach. This SNP has been associated with inflammatory bowel disease through GWAS, but it is not located near any gene related to this phenotype. However, geno 5 mC reveals that rs727563 is associated with the methylation state of several CpGs located in promoter regions of genes reported to be involved in inflammatory processes. This case exemplifies how geno 5 mC can be used to infer relevant and previously unknown interactions between described disease-associated SNPs and their functional targets.